The Problem of “Mental Harm” in the Genocide Convention - Stephen Gorove (Washington University Law Quarterly, 1951)
One of the most significant issues that has been raised by prominent American legal authorities in connection with the Genocide Convention centers around the concept of “mental harm.” What is meant by “mental harm” in the convention? Can “mental anguish,” “humiliation,” “mental distress,” discrimination of any kind be considered to constitute “mental harm”? Can the concept of “mental harm” be understood to mean the “disintegration of the mind” or is it rather identical with “permanent physical injury to mental faculties”? What are the necessary criteria, if any, of those acts which the Convention intends to punish in connection with mental harm? Since there seems to be no direct answer in the Convention to these very important issues, the authorities go even further by raising the question, how can the United States Senate give its consent to the ratification of this Convention and undertake by it to punish a crime, the meaning of which appears to be too elusive and vague? An inquiry into the fundamental issues relating to the concept of mental harm and a comparison between this concept as established by the Convention and somewhat similar notions of “mental anguish,” “grief,” “humiliation,” “mental distress,” etc.—well-known through a number of American court decisions and a series of international arbitral awards—is of paramount importance not only from the viewpoint of clarifying the intention of the Contracting Parties, but also from the viewpoint of any future judicial interpretation.
Keywords: Genocide